2019
DOI: 10.3382/ps/pez223
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus amyloliquefaciens CECT 5940 alone or in combination with antibiotic growth promoters improves performance in broilers under enteric pathogen challenge

Abstract: A study was conducted to investigate the effects of Bacillus amyloliquefaciens CECT 5940 as a direct-fed microbial (DFM) alone or in association with bacitracin methylene disalicylate (BMD) in broilers under enteric pathogen challenge. A total of 1,530-day-old male Cobb500 chicks were randomly assigned to 5 treatments, with 9 replicate pens with 34 birds each. Treatments included positive control (PC, basal diet without additives or challenge); negative control (NC, basal diet without additive and challenged b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 48 publications
2
25
0
1
Order By: Relevance
“…Improvements in live performance observed in this study were achieved by the addition of xylanase and DFM blend to broilers in a mild microbially-challenged environment. Results (BWG and FCR) at 35 and 42 days are in agreement with the findings of de Oliveira et al ( 32 ) when DFM were fed to broilers under enteric pathogen-challenged environment. Vandeplas et al ( 33 ) also reported an improvement in growth rate when a combination of Lactobacillus plantarum and xylanase was supplemented to broilers infected with Salmonella typhimurium .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Improvements in live performance observed in this study were achieved by the addition of xylanase and DFM blend to broilers in a mild microbially-challenged environment. Results (BWG and FCR) at 35 and 42 days are in agreement with the findings of de Oliveira et al ( 32 ) when DFM were fed to broilers under enteric pathogen-challenged environment. Vandeplas et al ( 33 ) also reported an improvement in growth rate when a combination of Lactobacillus plantarum and xylanase was supplemented to broilers infected with Salmonella typhimurium .…”
Section: Resultssupporting
confidence: 91%
“…Flock uniformity percentage at 21 days was more than 10%, which could be due to this being a straight-run flock (including both males and females); during the first 21 days, males and females differ in target organ nutrient deposition; males give priority for muscle accretion, mainly breast muscle, while females give priorities for feathering leading to a fully-feathered females by 21 days, whereas males become fully feathered by 35 days of age ( 35 ). By that time, fully-feathered females would have started depositing nutrients for muscle growth leading to overall improved flock uniformity seen at 35 and 42 days, which was similar to other researchers ( 32 ).…”
Section: Resultssupporting
confidence: 88%
“…These strains can also produce different bacteriocins, such as barnase and binase which can be effective in controlling C. perfringens [ 9 , 10 ]. Furthermore, the quorum quenching activity of BA can disturb the quorum sensing signaling molecules of some pathogenic bacteria, which is essential for the communication and growth of these microorganisms, and thereby inhibit the growth of the harmful groups [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, quorum sensing (QS) communication plays a key role in triggering the infectious activity of pathogenic bacteria, such as sporulation, biofilm formation, and virulence ( Cooksley et al, 2010 ). The BA strain can produce an enzyme, N-acyl-homoserine-lactone lactonase (AHL) ( Yin et al., 2010 ), which hydrolyses the QS signaling molecules of Gram-negative bacteria and disturb their pathogenic activities ( Alina et al., 2015 ; de Oliveira et al., 2018 ). The mechanism by which bacterial communication (QS) can be interrupted is referred to as quorum quenching (QQ).…”
Section: Discussionmentioning
confidence: 99%